Research of Prediction Method of Automobile Synchronous Belt Transmission Noise based on Orthogonal Test - Shi Yaochen; Li Zhanguo; Zhou Hong; Zhou Peng (Jixie chuandong)
The noise orthogonal test of the automotive synchronous belt transmission system is carried out based on two wheels of unloaded test method. The influence law of the three parameters of the active wheel speed,synchronous belt bandwidth and tensioning force on the synchronous belt transmission noise is analyzed systematically. The orthogonal table is extended by regression,without any increase in testing time,a regression mathematical model is established based on the objective function of automobile synchronous belt transmission,and the accuracy of the mathematical model is verified by experiment. A method for the research of the influence factors of transmission noise of automobile synchronous belt is provided,and the prediction of transmission noise of automobile synchronous belt is realized.